Experience of the multidisciplinary team of the rehabilitation department in the rehabilitation treatment of post-stroke patients with psychosomatic manifestations - Forduk Наталія; Dotsjuk ВВ; Moisjuk ЗМ; Polishchuk Олександр; Amelina ТМ (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the ІV Scientific and Practical Conference "Psychosomatic medicine: science and practice". It is dedicated to the experience of the multidisciplinary team of the rehabilitation department in the rehabilitation treatment of post-stroke patients with psychosomatic manifestations